Comparison between Local Infiltration Combination of 1% 200 mg Lidocaine and 10 mg Dexametason with 0.75% 150 mg Ropivacaine on Degree of Pain in Post-Caesarian Operative Wounds - Simamora, Veronica; Bangun, Chrismas Gideon; Hamdi, Tasrif; Harahap, Juliandi (Jurnal Anestesi Perioperatif, 2025)
Introduction: Local anesthetic wound infiltration reduces postoperative pain, promotes early mobilization, and shortens hospital stay after cesarean section. Lidocaine is widely used, and the addition of dexamethasone may prolong its analgesic effect. Ropivacaine provides longer-lasting analgesia but is more expensive and less accessible in many hospitals. This study aimed to compare the analgesic effects of local wound infiltration using 0.75% ropivacaine 150 mg versus 1% lidocaine 200 mg combined with 10 mg dexamethasone on postoperative pain following cesarean section. Methods: This randomized, double-masked, controlled clinical trial involved 38 patients undergoing cesarean section under spinal anesthesia. Participants were randomly allocated using a computer-generated sequence to receive wound infiltration with either 1% lidocaine (200 mg) plus dexamethasone (10 mg) or 0.75% ropivacaine (150 mg). Patients and outcome assessors were blinded to group allocation. Postoperative pain intensity was assessed using the Numeric Rating Scale (NRS) at rest and during passive movement at 2, 6, 12, and 24 hours after surgery. Results: The ropivacaine group had significantly lower NRS scores at rest and during passive movement at 2, 6, and 12 hours postoperatively compared with the lidocaine–dexamethasone group (p < 0.05). At 24 hours after surgery, no significant difference in pain intensity was observed between groups (p>0.05). Conclusion: Local wound infiltration with 0.75% ropivacaine 150 mg provided superior analgesia during the first 12 hours after cesarean section compared with lidocaine combined with dexamethasone. The lidocaine–dexamethasone combination remains a practical alternative where ropivacaine is unavailable.